On the statistics of insanity, past and present - Corbet, William J. (Statistical and Social Inquiry Society of Ireland, 1874)
At this particular juncture in our social existence, when mental culture?the development of the intellectual faculties of mankind? claims pre-eminent consideration on all sides, and fills with anxiety the minds of the profoundest thinkers, the foremost statesmen, and the most disinterested philanthropists of the age; when primary, intermediary, and university education are the watchwords of the sentinels who keep guard over the rights and privileges of the people, it cannot be uninteresting briefly to consider what is the mental condition of the masses who are to be affected by such beneficent intentions; whether, in fact, the familiar phrase ?mens sana in corpore sano?, which embraces so much?expressing as it does, when applied to individuals, the ?summum bonum?, the perfection of physical and intellectual well-being, can at this moment be fitly used to express the condition of the mass of mortality signified by the noun of multitude??public?.
Read before the Society, 21 April 1874
Keywords: Insanity statistics in Ireland; Mental health; 314.15